Design and performance evaluation of Advanced Priority Based Dynamic Round Robin Scheduling Algorithm (APBDRR) - Saha, Debasmita; Mandal, Ardhendu (International Journal of Computer Sciences and Engineering, 2025)
In this paper we have proposed a improvised version of Round Robin Scheduling Algorithm by calculating Dynamic Time Quantum (DTQ) and taking into consideration the priorities assigned with the processes. We have compared the performance of the proposed Advanced Priority Based Dynamic Round Robin Scheduling Algorithm (APBDRR) with the performances of Round Robin Algorithm (RR), Improved Shortest Remaining Burst Round Robin Algorithm (ISRBRR) and Efficient Dynamic Round Robin Algorithm (EDRR). Experimental results show that the proposed algorithm performs better than these algorithms in terms of Average Waiting Time(AWT) and Average Turnaround Time(ATAT).